2010
DOI: 10.1007/s10870-010-9765-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral and Structural Studies of a Novel Semicarbazone Synthesized from Quinoline-2-Carboxaldehyde and N4-Phenyl-3-Semicarbazide

Abstract: A new semicarbazone, HL has been synthesized from quinoline-2-carboxaldehyde and N 4-phenyl-3semicarbazide and structurally and spectrochemically characterized. 1 H NMR, 13 C NMR, IR and electronic spectra of the compound are studied. The existence of keto form in the solid state is supported by the crystal structure and IR data. The compound crystallizes into an orthorhombic space group P2 1 2 1 2 1. Intra and intermolecular hydrogen bonding interactions facilitates unit cell packing in the crystal lattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The existence of semicarbazone in the amido form in the solid state is confirmed by the observed bond length of 1.210 (2) Å for C8-O3 bond which is identical to a formal C=O bond length [1.21 Å] (Kala et al, 2007). The N1-N2 and N2-C8 bond distances of 1.364 (2) Å and 1.377 (2) Å respectively are greater than that for a double bond and less than that for a single bond which indicate appreciable delocalization of π-electron density over the semicarbazone chain (Reena & Kurup, 2010). Rings Cg1 ii (comprising atoms C1-C6) and Cg2 iii (comprising atoms C9 -C14) make a dihedral angle of 14.43 (12)° with each other while rings Cg1 ii and Cg3 iv (comprising atoms C15-C20) are twisted away from each other by a dihedral angle of 88.60 (12)° [symmetry codes:…”
Section: Data Collectionmentioning
confidence: 77%
See 1 more Smart Citation
“…The existence of semicarbazone in the amido form in the solid state is confirmed by the observed bond length of 1.210 (2) Å for C8-O3 bond which is identical to a formal C=O bond length [1.21 Å] (Kala et al, 2007). The N1-N2 and N2-C8 bond distances of 1.364 (2) Å and 1.377 (2) Å respectively are greater than that for a double bond and less than that for a single bond which indicate appreciable delocalization of π-electron density over the semicarbazone chain (Reena & Kurup, 2010). Rings Cg1 ii (comprising atoms C1-C6) and Cg2 iii (comprising atoms C9 -C14) make a dihedral angle of 14.43 (12)° with each other while rings Cg1 ii and Cg3 iv (comprising atoms C15-C20) are twisted away from each other by a dihedral angle of 88.60 (12)° [symmetry codes:…”
Section: Data Collectionmentioning
confidence: 77%
“…For applications of hydrazinecarboxamide and its derivatives, see: Afrasiabi et al (2005); Alam et al (2010). For related structures, see: Siji et al (2010); Reena & Kurup (2010); Sithambaresan & Kurup (2011). For standard bond-length data, see: March (1992); Kala et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…These two intramolecular hydrogen bonding interactions play an important role by stabilizing this conformation. The C8-N2 bond distance [1.3656 (19) Å] is appreciably close to that of C-N single bond [1.351 (2) Å], confirming the keto form of the ligand (Reena & Kurup, 2010). The existence of 2-(3-ethoxy-2-hydroxybenzyl)-N-phenylhydrazinecarboxamide in the keto form in the solid state is evidenced by the C8-O2 bond distance of 1.2233 (19) Å, which is very close to a formal C=O bond length [1.21 Å] (Kala et al, 2007).…”
Section: S1 Commentmentioning
confidence: 80%
“…Semicarbazones can function as brilliant ligands in a variety of metal ions (Kala et al, 2007) and co-ordinate to metal ions either in neutral (Siji et al, 2011) or in anionic forms (Reena et al, 2008). Structural studies of many semicarbazones and N 4 -phenylsemicarbazones have been reported and some of them adopt an E configuration with respect to the azomethine double bond along with both inter-and intramolecular hydrogen-bonding interactions (Reena et al, 2010;Layana et al, 2014Layana et al, , 2018. Semicarbazones form complexes with a variety of structural ISSN 2056-9890 features such as monomer, dimer and one-dimensional polymers (Kunnath et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%